A unified approach to exponential stability analysis for a general class of switched time-delay linear systems - Khoa Son, Nguyen; Le, Ngoc Van (Journal of Computer Science and Cybernetics, 2021)
This paper proposes a unified approach to study global exponential stability for a class of switched time-delay linear systems described by general linear functional differential equations. Several new delay-dependent criteria of exponential stability are established for this class of systems, under arbitrary switching which satisfies some assumptions on the minimum dwell time or the average dwell time. As particular cases, the obtained results are shown to include and improve many previously known results. An example is given to illustrate the proposed method.